Performance evaluation of a continuous packed bed bioreactor: Bio-kinetics and external mass transfer study - Sonwani R.K.; Giri B.S.; Jaiswal R.P.; Singh R.S.; Rai B.N. (My University, 2025)
The biodegradation of naphthalene using low-density polyethylene (LDPE) immobilized Exiguobacterium sp. RKS3 (MG696729) in a packed bed bioreactor (PBBR) was studied. The performance of a continuous PBBR was evaluated at different inlet flow rates (IFRs) (20–100 mL/h) under 64 days of operation. The maximum naphthalene removal efficiency (RE) was found at low IFR, and it further decreased with increasing IFRs. In a continuous PBBR, the external mass transfer (EMT) aspect was analysed at various IFRs, and experimental data were interrelated between Colburn factor (JD) and Reynolds number (NRe) asJD=KNRe(n−1). A new correlation JD=5.71NRe−0.1 was obtained to predict the EMT aspect of naphthalene biodegradation. Andrew–Haldane model was used to evaluate the bio-kinetic parameters of naphthalene degradation, and kinetic constant νmax, Js, and Ji were found as 0.386 per day, 13.6 mg/L, and 20.54 mg/L, respectively. © 2020